Leptospira seropositivity as a risk factor for Mesoamerican Nephropathy. (2nd January 2017) - Riefkohl, Alejandro; Ramírez-Rubio, Oriana; Laws, Rebecca L.; McClean, Michael D.; Weiner, Daniel E.; Kaufman, James S.; Galloway, Renee L.; Shadomy, Sean V.; Guerra, Marta; Amador, Juan José; Sánchez, José Marcel; López-Pilarte, Damaris; et al.
Abstract: Background: Leptospirosis is postulated as a possible cause of Mesoamerican Nephropathy (MeN) in Central American workers. Objectives: Investigate job-specific Leptospira seroprevalence and its association with kidney disease biomarkers. Methods: In 282 sugarcane workers, 47 sugarcane applicants and 160 workers in other industries, we measured anti-leptospiral antibodies, serum creatinine, and urinary injury biomarkers, including neutrophil gelatinase-associated lipocalin (NGAL), interleukin-18 (IL-18), and N-acetyl-D-glucosaminidase (NAG). Results: Leptospira seroprevalence differed among job categories and was highest among sugarcane cutters (59%). Seropositive sugarcane workers had higher NGAL concentrations (relative mean: 1.28; 95% CI: 0.94–1.75) compared to those who were seronegative, with similar findings among field and non-field workers. Conclusions: Leptospira seroprevalence varied by job category. There was some indication that seropositivity was associated with elevated biomarker levels, but results were inconsistent. Additional studies may help establish whether Leptospira infection plays any role in MeN among Central American workers.